Optimasi PV Array Menggunkan Maximum Power Point Tracking dengan Algoritma FireFly dan Partical Swarm Optimization kondisi Normal dan Partial Shadding - Hasan, Fuad; ., Muhyidin; Faturrahman, MMoh. Andy (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
Most solar power plants are not capable of operating independently at maximum capacity, the voltage characteristics of solar energy usually follow the voltage (V) of the storage (battery) or load (load) which is directly connected to solar energy. Of course, the irradiation received by the PV module does not always receive uniform radiation so that the power produced does not always have maximum power and causes double peaks. An MPPT (Maximum Power Point Tracking) system is required to optimize PV output. However, the commonly used methods are often trapped by peaks below the optimal peak and require a long convergence time. This research compares the tracking performance and tracking time of two methods, FF (Firefly Algorithm) and PSO (Particle Swarm Optimization), to find the best performance in partial shadow conditions. The PSO algorithm has an average efficiency of 99.1043% and the FF algorithm has an average efficiency of 99.4073% in 10 trials in each of the 6 cases.